Polyphenylene sulfide woven fabric

JP2025029794AActive Publication Date: 2025-03-07TOYOBO FIBER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023134621
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07
Estimated Expiration
2043-08-22

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、スクリーン、フィルター、濾過布、ストレーナ、電池セパレータなどの電気絶縁材に好適な、PPS繊維からなる繊維製品を高品質で尚且つ、安全、安定に提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029794000001
    Figure 2025029794000001
Patent Text Reader

Abstract

To provide a woven fabric obtained by using a PPS filament in at least part, and suitable as a screen, a filter, and an electric insulating material.SOLUTION: There is provided a woven fabric including a PPS filament yarn having a single filament fineness of 2-50 dtex, the number of constituent single filaments of 1-4 and a total fineness of 2-200 dtex as the warp and / or the weft, and obtained by using a linear type PPS resin as a raw material for the PPS filament, in which the maximum value Tan δ max of the dynamic loss tangent Tan δ in a measurement frequency of 0.5 Hz, which is a viscoelastic structural parameter of the amorphous region of the PPS filament, is 0.02-0.05; the atmospheric temperature T max when Tan δ shows the maximum value is 130-160°C; and the tensile strength and elongation specified in JIS L1013.8.5.1 (test at standard atmospheric condition) has a stress-strain curve having a yield point and a breaking elongation of 15-35%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a woven fabric using polyphenylene sulfide (hereinafter, also referred to as PPS) fibers. The PPS woven fabric of the present invention is woven using PPS long fiber filaments that meet specific conditions for at least a part of the fabric, and can be suitably used as a screen, a filter, a filter cloth, or an electrical insulating material. [Background technology]

[0002] PPS fiber has excellent heat resistance, chemical resistance, and flame retardancy, which are inherent to PPS. Taking advantage of these characteristics, it is used in a wide range of applications, including various filters, electrical insulation materials, printing screens, and battery separators.

[0003] PPS resin is broadly divided into two types: crosslinked PPS and linear PPS, with the highly tough linear type being used for fibers. PPS resin can be manufactured by dissolving sodium sulfide in a polar solvent such as N-methylpyrrolidone and carrying out a polycondensation reaction with paradichlorobenzene. The resulting pellets are melt-spun to produce staple fibers, spunbond nonwoven fabrics, multifilament yarns, and monofilament yarns. The reaction products of PPS resin contain a variety of by-products and impurities, so the cost of the refining process currently accounts for a large portion of the manufacturing cost.

[0004] The glass transition temperature of PPS fiber is approximately 80-90℃, the melting point is 280-290℃, and other physical properties are similar to those of polyethylene terephthalate (PET), which is also a semi-crystalline material, but during melt spinning, the PPS resin and oligomer components thermally decompose, generating toxic and highly corrosive acidic gases containing sulfur and chlorine, which not only corrode metal materials such as polymer piping, extruder barrels, screws, and spinning nozzles, but also may harm the health of workers. After melt spinning, in order to prevent piping corrosion due to residual PPS resin, it is necessary to replace and clean the resin flow path (polymer line) with general-purpose resins such as PET resin and polypropylene resin to completely drain the remaining PPS resin, and there are many points to keep in mind when manufacturing PPS fiber, making it one of the synthetic resin materials that require careful care in terms of maintenance and management.

[0005] For fibers and fiber structures using PPS resin, various manufacturing methods have been proposed and are on the market. For example, Patent Document 1 proposes a manufacturing method of PPS long fiber nonwoven fabric by the spunbond method. Specifically, the technology discloses that a resin mainly composed of PPS is discharged from a spinneret, then pulled and stretched by an ejector at a spinning speed of 3000 m / min or more, collected on a net to form a nonwoven fabric web, and then the nonwoven fabric web is thermally welded using an embossing roll, making it possible to obtain a nonwoven fabric with a small fiber diameter and excellent thermal stability by a simple process. However, long fiber nonwoven fabrics using the spunbond method have the disadvantages of low tear strength and breaking elongation, difficulty in following even small bending deformation, and large variations in basis weight and thickness.

[0006] Patent Document 2 also proposes a method of using staple fibers made of PPS resin to make spun yarn, which is then woven into a fabric, and then hydrophilized. This method is not a problem for applications such as separators that are impregnated with resin, or for applications such as electrical insulators, but when used for filters, there is a concern that the staple fibers may be easily removed or may be contaminated by being cut or dropped off, since the staple fibers are end-ended fibers. In addition, in applications such as filter press filtration cloth applications, water drainage and cake separation are poor. Therefore, this method cannot be said to be preferable for screen, filter, or filtration cloth applications.

[0007] Furthermore, Patent Document 3 proposes an SMS laminated nonwoven fabric or an SMS laminated nonwoven fabric, which is formed by laminating a spunbonded nonwoven fabric using a PPS resin and a meltblown nonwoven fabric. Here, S refers to spunbond, and M refers to meltblown. This method enables precise filtration of gases and liquids, which is preferable in terms of cost and production efficiency, but has the disadvantage that the multi-layer laminate is thick and difficult to follow even small bending deformations. In addition, the use of a meltblown nonwoven fabric alone is also possible. In this case, it has the properties of being highly flexible and easily following small bending deformations, but it is thin, easily charged, and weak in strength, so technical know-how is required for handling and workability. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] WO2011 / 070999 publication [Patent Document 2] Patent Publication No. 2018-534441 [Patent Document 3] WO2008 / 035775 publication Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made to solve the problems of the conventional art as described above, and an object of the present invention is to provide a woven fabric at least in part using PPS long fiber filaments, which is suitable as a material for screens, filters, filtration cloths, strainers, and electrical insulating materials, and a composite material using the same. [Means for solving the problem]

[0010] As a result of intensive research into solving the above problems, the inventors have discovered that by controlling the characteristic values ​​of the long fiber filaments made of PPS resin, which is the raw material, within certain ranges, it is possible to provide woven fabrics that are not only high quality but also satisfy product safety, production costs and production stability, and have completed the present invention.

[0011] The present invention has the following configurations (1) to (7). (1) A woven fabric comprising polyphenylene sulfide long fiber filaments having a single yarn size of 2 dtex or more and 50 dtex or less, a single yarn number of 1 to 4, and a total size of 2 dtex or more and 200 dtex or less arranged in the warp and / or weft, the polyphenylene sulfide long fiber filaments being made of linear polyphenylene sulfide resin, the maximum value Tanδmax of the mechanical loss tangent Tanδ at a measurement frequency of 0.5 Hz, which is a viscoelastic structural parameter of the amorphous region of the polyphenylene sulfide long fiber filaments, being 0.02 to 0.05, the ambient temperature Tmax at which Tanδ is maximum is 130°C to 160°C, and the JIS A polyphenylene sulfide fabric characterized in that the stress-strain curve of the polyphenylene sulfide long fiber filament has a yield point and the breaking elongation is 15% or more and 35% or less in the tensile strength and elongation specified in L1013.8.5.1 (standard time test). (2) A polyphenylene sulfide woven fabric according to (1), characterized in that the polyphenylene sulfide long fiber filaments have a circular cross section, a single fiber diameter of the polyphenylene sulfide long fiber filaments is 15 μmφ or more and 70 μmφ or less, and a birefringence Δn of the polyphenylene sulfide long fiber filaments is 0.100 or more and 0.300 or less. (3) The polyphenylene sulfide fabric according to (1), characterized in that the polyphenylene sulfide fabric has a weave structure of any one of plain weave, twill weave, and satin weave, the mesh size of the polyphenylene sulfide fabric is 1 μm or more and 200 μm or less, and the opening ratio of the polyphenylene sulfide fabric is 10% or more and 60% or less. (4) A polyphenylene sulfide fabric according to any one of (1) to (3), characterized in that, when the polyphenylene sulfide fabric is placed horizontally and stationary, the variation in opening rate before and after dry heat treatment for 30 minutes at a treatment temperature of 160°C is within ±3%, and the weight change rate after immersing the polyphenylene sulfide fabric for 24 hours in each of cyclohexanone and isophorone solvents in an environment of a temperature of 20±2°C and a relative humidity of 65±5%RH is less than 3.0% in both cases. (5) A screen characterized by using the polyphenylene sulfide fabric described in (1). (6) A filter using the polyphenylene sulfide fabric described in (1). (7) An electrical insulating material using the polyphenylene sulfide fabric described in (1). Effect of the Invention

[0012] According to the present invention, it is possible to provide high-quality, safe and stable textile products made of PPS fibers suitable for electrical insulating materials such as screens, filters, filter cloths, strainers, and battery separators. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The PPS woven fabric of the present invention is formed by arranging, in the warp and / or weft, PPS long fiber filaments having a single fiber fineness, a number of constituent single fibers, and a total fineness within specific ranges, and the PPS long fiber filaments are made from linear polyphenylene sulfide resin.

[0014] The single yarn fineness of the PPS long fiber filament is in the range of 2 dtex to 50 dtex, more preferably 3 dtex to 40 dtex, and even more preferably 5 dtex to 35 dtex. An ultrafine yarn having a single yarn fineness below the above range cannot maintain the mechanical strength required for the expected applications, and conversely, if it is significantly above the above range, the fiber becomes very rigid, and the obtained fiber structure tends to be difficult to bend and deform.

[0015] The number of constituent single yarns of the PPS long fiber filament is in the range of 1 to 4, preferably 1 to 3. If the number of constituent single yarns is more than the above range, the specific surface area increases, and when used for liquid filtration filters or strainers, the ability to capture impurities improves. However, if the fluid contains a large amount of impurities, it becomes difficult to remove the impurities by backwashing, and the pressure loss increases over time, resulting in an early end of the filter life. As a result, this leads to more frequent filter replacement and higher running costs.

[0016] The total fineness of the PPS long fiber filaments is in the range of 2 dtex to 200 dtex, preferably 3 dtex to 100 dtex, and more preferably 3 dtex to 50 dtex. If the total fineness is less than the above range, the strength required for filter, strainer, and screen applications cannot be ensured, while if it exceeds the above range, the mesh size becomes large when woven into a filter, strainer, screen, etc., and the impurity capture effect tends to be reduced.

[0017] In the PPS woven fabric of the present invention, PPS long fiber filaments are used in all or at least a part of the warp and / or weft. More preferably, PPS long fiber filaments are used in all of the warp and / or weft, and even more preferably, PPS long fiber filaments are used in all of the warp and weft. Of course, it is possible to alternately arrange one long fiber filament other than PPS and one PPS long fiber filament in each of the warp and / or weft, and it is also possible to use filaments having different finenesses. Examples of long fiber filaments other than PPS that can be suitably combined with the PPS long fiber filaments include known filaments such as polyethylene terephthalate (PET), polyvinylidene chloride (PVDC), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), aromatic polyamide (PPA), polyetherimide (PEI), polyamideimide (PAI), polyether ether ketone (PEEK), and polycarbonate (PC).

[0018] PPS resin is a crystalline heat-resistant polymer, and is widely recognized as an engineering plastic that exhibits chemical resistance, flame retardancy, advanced mechanical properties, and excellent dimensional stability. Commercially available polymer PPS resins are of crosslinked and linear (linear, straight-chain) types. The former exhibit high rigidity even in high temperature ranges and are advantageous against creep deformation, and are used for injection molded products, while the latter are characterized by elongation and toughness, and are used for fibers, etc. The PPS long fiber filament of the present invention uses linear PPS resin as a raw material.

[0019] The maximum value Tanδmax of the mechanical loss tangent Tanδ at a measurement frequency of 0.5 Hz, which is a viscoelastic structural parameter of the amorphous region of the PPS long fiber filament used in the PPS woven fabric of the present invention, is 0.02 to 0.05, preferably 0.02 to 0.04. The mechanical loss tangent Tanδ is the ratio of the storage modulus E' to the loss modulus E'' (Tanδ=E' / E'') and is a measure of the thermal mobility of the amorphous tie molecules constituting the amorphous region. The lower the value of Tanδ, the more the crystallization and crystal orientation progress, the more stable the structure is, and the more the mechanical properties and heat resistance are improved. If Tanδmax exceeds the above range, the dimensional stability and mechanical strength tend to remain low. If Tanδmax is less than the above range, the toughness tends to remain low, and there is a high possibility of problems such as being easily brittle fractured.

[0020] In addition, the ambient temperature Tmax when the maximum value Tanδmax of the mechanical loss tangent is shown is in the range of 130°C or more and 160°C or less, preferably 135°C or more and 155°C or less. Tmax also shifts to the high temperature side by promoting crystallization. If Tmax is equal to or higher than the lower limit temperature of the above range, the crystallization and oriented crystallization are advanced, and the mechanical strength and thermal stability are also in a range preferable for the expected application, and the boiling water shrinkage of the woven fabric can be suppressed low. Tanδmax and Tmax can be controlled by a combination of drawing conditions such as the draw ratio, drawing temperature, drawing speed, and heat setting temperature during the production of PPS long fiber filament, and the molecular weight of the PPS resin used. In particular, the higher the draw ratio, heat setting temperature, and molecular weight of the PPS resin, the smaller the value of Tanδmax and the larger the value of Tmax. In addition, the mesh size can be stabilized, and the quality of the woven fabric can be improved. If the upper limit temperature of the above range is exceeded, the toughness remains low. Toughness is a material term meaning that both strength and ductility are high, but in the region exceeding the upper limit of the temperature range, the ductility is low and the material becomes brittle. Conversely, in the range below the lower limit of the above range, the ductility is high but the strength is low, which is undesirable.

[0021] The cross section of PPS long fiber filament is preferably round, which maximizes the tenacity utilization rate. Triangular, flat, multi-lobed, and hollow cross section yarns can be produced by changing the spinneret equipment, but the physical properties of the resulting yarn, such as tensile strength and elongation, tend to remain low compared to the same fineness of high-polymerization PET long fiber filament, which is a general-purpose resin.

[0022] The single fiber diameter of the PPS long fiber filament is in the range of 15 μmφ to 70 μmφ, more preferably 20 μmφ to 60 μmφ, and even more preferably 30 μmφ to 60 μmφ. If the single fiber diameter is less than the above range, the fiber is likely to be cut due to abrasion damage, which is not preferable considering the intended use of the present invention. If the single fiber diameter exceeds the above range, the fiber becomes very rigid and may be used in some industrial material applications, but it is difficult to say that the single fiber diameter is suitable for the intended use of the present invention.

[0023] The birefringence Δn of the PPS long fiber filament is preferably in the range of 0.100 to 0.300, more preferably 0.150 to 0.300, and even more preferably 0.200 to 0.250. The birefringence Δn is a substitute characteristic for the degree of crystal orientation in the fiber axis direction, and the value increases as the draw ratio increases. If the birefringence Δn is less than the above range, the degree of crystal orientation is small and the yarn strength is likely to be poor. If it exceeds the above range, the yarn strength is high, but the ductility and toughness are likely to be poor. By controlling the birefringence Δn within the above range, the physical properties (toughness) and thermal properties of the fiber are also improved, making it suitable for use in the applications intended by the present invention.

[0024] The weight average molecular weight of the PPS resin used in the present invention is preferably 20,000 or more, more preferably 25,000 or more, and even more preferably 30,000 or more. By making the weight average molecular weight 30,000 or more, mechanical properties such as thread strength and toughness, heat resistance, and chemical resistance become good. In order to obtain good melt spinnability, the upper limit of the weight average molecular weight is preferably 150,000 or less, more preferably 120,000 or less, and even more preferably 100,000 or less. In particular, when the weight average molecular weight is 40,000 to 80,000, it is easy to control Tan δmax and Tmax within the above-mentioned appropriate range. The weight average molecular weight can be calculated in terms of polystyrene, for example, by the method described in the Examples.

[0025] In addition, the stress-strain curve of the PPS long fiber filament has a yield point and a breaking elongation of 15% to 35%, preferably 20% to 30%, in the tensile strength and elongation (standard time test) specified in JIS L1013.8.5.1. The stress-strain curve having a yield point means that the curve has either "only an upper yield point" or "an upper yield point, a lower yield point, and a yield shelf". The upper yield point and the lower yield point are defined in 1162 and 1162 of the "tensile test" in the "mechanical test" of JIS G 0202. If the curve does not have a yield point, the filament has poor toughness. Toughness is "tenacity", and a material with poor toughness does not follow elongation deformation and is prone to brittle fracture. It is desirable that the PPS long fiber filament used in the PPS fabric of the present invention has a yield point and is rich in toughness. The upper yield point of the PPS long fiber is preferably at an elongation of 2% to 20%, and more preferably at an elongation of 3% to 10%. When the upper yield point appears within this range of elongation, the toughness of the yarn is improved, and the yarn becomes soft, has high tensile strength and elongation, and has excellent strength, which tends to improve the quality of the weave. The yield point and breaking elongation can also be controlled by a combination of drawing conditions such as the draw ratio, drawing temperature, drawing speed, and heat setting temperature during the production of the PPS long fiber filament, and the molecular weight of the PPS resin used. In particular, an excessively large draw ratio is not preferable because it does not have a yield point and has a small breaking elongation. It is essential to determine an appropriate combination of drawing conditions while taking into account the fineness after drawing.

[0026] PPS long fiber filaments can be produced by conventional melt spinning or air gap spinning. In particular, when the single fiber fineness is large, air gap spinning is effective in preventing operational and quality problems such as cooling efficiency and adhesion of fibers. In addition, spinning and drawing can be carried out using known techniques such as the so-called spin-draw method in which spinning and drawing are directly connected, or a two-step method in which spinning and drawing are separated into two steps.

[0027] In addition to the usual dry drawing, the drawing process can also suitably be performed in a bath (draw bath drawing) in which drawing is performed in a heat medium such as hot water controlled to a temperature equal to or higher than the glass transition temperature of the long fiber filament, or in a zone drawing method. The drawing process can be performed in one stage or multiple stages. Since the thermal shrinkage stress is high after the drawing process, it is more preferable to reduce the thermal shrinkage stress by performing a relaxation heat treatment under hot roller heating or steam heating. Furthermore, in consideration of the efficiency of the spinning process, it is also possible to obtain a desired long fiber filament by performing the spinning drawing process in the multifilament state, and then dividing it into a single yarn (one yarn) or several yarns using a fiber splitter. There is no limitation on the winding shape of the filament, and in addition to cheese winding around a paper tube, known winding shapes such as warp winding, filling winding, and compound winding around a metal or resin bobbin can be adopted. In particular, when the fiber has a large fineness, the contact area between the fibers becomes small and the fibers tend to slip when wound, so it is preferable to use a single flange type or double flange type bobbin.

[0028] As described above, the stretching process may be performed in one stage or multiple stages. In the case of multiple stages, the total stretch ratio, which is the sum of the stretch ratios, is preferably 1.5 to 6.0. More preferably, it is 2.5 to 5.5, and even more preferably, it is 2.8 to 5.2. By setting the total stretch ratio within this range, the yield point can be created and the breaking elongation can be set to an appropriate range. If the stretch ratio is less than 1.5, the breaking elongation becomes too high and the birefringence becomes low, which may make it difficult to obtain practical yarn strength. If the total stretch ratio exceeds 6.0, the yield point may disappear and the breaking elongation may decrease, resulting in poor toughness.

[0029] The boiling water shrinkage of the PPS woven fabric (grey fabric) of the present invention is preferably -3% to 3%, more preferably -2.5% to 2.5%, and even more preferably -2.0 to 2.5%. By setting the boiling water shrinkage of the grey fabric within the above range, it is possible to suppress fluctuations in the aperture ratio during use at high temperatures as a filter product, and it is possible to exhibit stable and precise filter performance.

[0030] The weave of the PPS fabric of the present invention is preferably composed of any one of plain weave, twill weave, and satin weave. Plain weave includes plain weave such as stone weave and diagonal weave, which are woven by aligning multiple warp threads and / or weft threads. Preferred examples of twill weave include 2 / 1 twill, 3 / 1 twill, 2 / 2 twill, 3 / 2 twill, 3 / 3 twill, 3 / 1 broken twill, and herringbone weave in which the twill direction is changed at a constant interval. Satin weave includes five-ply warp twill such as 4 / 1 and 3 / 2, five-ply twill such as five-ply weft twill, seven-ply twill, eight-ply twill, and both-sided twill weaves of these. In the case of satin weave, even if the five-ply warp twill is the same 4 / 1, there are multiple types such as two-ply and three-ply, depending on the number of steps, but all are included. The optimal weave can be selected depending on the purpose and use. For example, when used for liquid / solid separation, particularly filtration with a high solid content, a satin weave that has good cake release is preferred, while when used for gas / solid separation with a low solid content, a plain weave or twill weave that has low pressure loss is preferred.

[0031] The finishing density of the PPS woven fabric of the present invention after scouring and heat setting is preferably 120 threads / 2.54 cm or more and 320 threads / 2.54 cm or less for both warp and weft. If the finishing density is less than the above range, the mesh size is too large and the filtration performance is not fully exhibited. If the finishing density is more than the above range, the mesh size is low and clogging is likely to occur. The balance of the warp and weft densities (warp density / weft density) is preferably 1.3 to 0.9 in the case of plain weave or twill weave. If it exceeds 1.3 or is less than 0.9, there is a risk of a decrease in precise filtration performance. In the case of satin weave, the density of the warp to the weft (warp density / weft density) or the density of the weft to the warp (weft density / warp density) is preferably 1.8 to 3.0. Outside this range, it is difficult to obtain stable filtration performance.

[0032] The weave of the present invention is not limited to the above, and may be appropriately combined depending on the application, or multiple sheets of the same or different weaves may be used in layers depending on the application. When multiple sheets are used in layers, the filtration efficiency can be further improved by changing the crossing angle between the sheets, for example, to 45°. Twill weave is effective when the fiber diameter is large compared to plain weave, and is appropriately adopted depending on the fiber used and the desired performance.

[0033] In addition, the PPS fabric of the present invention preferably has an opening size of 1 μm or more and 200 μm or less, and an opening ratio of 10% or more and 60% or less. If the opening size is less than the above range, the filtration efficiency increases, but the mesh easily clogs, and the time required for filtration is likely to be long. If it exceeds the above range, the opening size becomes too large and coarse, and there is a risk that sufficient filtration and separation cannot be performed. If the opening ratio is less than the above range, the filtration efficiency decreases, and there is a risk that blockage and clogging occur easily. Conversely, if it exceeds the above range, there is a risk that the mesh is too coarse, and there is a risk that sufficient filtration and separation cannot be performed.

[0034] Weaving can be carried out using known looms such as air jet looms, water jet looms, rapier looms, projectile looms, needle looms, shuttle looms, etc. As for the warping step, which is a weaving preparation step, in addition to partial warping using a partial warper, rough warping using a warper and a beamer, a method of directly supplying warp yarns from yarns arranged in a weaving yarn creel to a loom without going through the warping step and weaving can also be used.

[0035] The obtained grey fabric is processed into the textile product of the present invention through processes such as scouring, washing, drying, and heat setting in the usual manner. Although known equipment can be used for each of the above processes, as the mesh size is large and fabric is prone to twisting and wrinkling, it is more suitable to process the fabric in an open state using a beam-to-beam system. In this process, it is important to avoid applying excessive tension and to straighten the fabric while processing in order to ensure the quality and yield of the product.

[0036] The obtained product is wound into a roll, slit-cut according to the specified width, and supplied to the customer. The cutting is performed using a known welding method such as an ultrasonic welder or high-frequency welder, which makes it possible to prevent fraying of the cut edges.

[0037] By configuring the PPS fabric of the present invention as described above, the variation rate of the opening rate before and after dry heat treatment at 160°C for 30 minutes in a horizontal stationary state can be within ±3%, preferably within ±2.5%, and more preferably within ±2.2%. The opening rate is an important characteristic in applications such as printing screens and filter cloths, and it is preferable that the variation rate, that is, the change in the opening rate due to temperature, is small. If the variation rate of the opening rate exceeds the above range, the size of the captured particles, that is, the filtration diameter, also changes significantly, which is likely to cause a decrease in filtration accuracy.

[0038] The solvent used in solvent-based screen ink must be a good solvent for the binder resin. Examples include glycol ether solvents, ester solvents, ketone solvents, aliphatic solvents, aromatic solvents, alcohol solvents, and ether solvents, and two or more of these can be mixed together as necessary. However, if the boiling point of the solvent used in solvent-based screen ink is too low, it will dry on the screen plate and is not suitable for printing. In terms of workability and print quality, it is preferable to use solvents with a melting point of around 200°C, such as cyclohexanone, which has a boiling point of about 155°C, and isophorone, which has a boiling point of about 215°C, for screen printing ink.

[0039] The PPS fabric of the present invention is characterized in that after immersion for 24 hours in both of the above-mentioned solvents, cyclohexanone and isophorone, which are classified as cyclic ketones, at a temperature of 20±2°C and a relative humidity of 65±5%RH, the weight change rate is less than 3.0%, that is, the weight change rate due to swelling or dissolution is less than 3.0%, and the change in mesh size is small. In addition, PPS resin is generally a crystalline polymer with a crystallinity of 40 to 60%, and the solvent may penetrate into crazes that occur in areas where stress is concentrated, such as the weave points of the fabric, causing solvent cracks, which may grow and lead to breakage. Therefore, it is necessary to set conditions such that the tension applied during weaving is low and the density and structure of the fabric are appropriately combined to a range in which crazes do not occur and brittle fracture does not occur.

[0040] The components other than the solvent contained in the solvent-based screen ink are color materials such as organic and inorganic pigments and dyes, metal powders such as aluminum and brass in the case of glitter printing, solid fine particles such as silica, binder resins such as urethane resins and acrylic ester resins, and crosslinking agents such as blocked isocyanates. The viscosity, penetration into the substrate, drying, etc. of the ink change depending on the mixing ratio and temperature of each agent, the type of solvent, the formulation amount, etc. It is desirable to adjust appropriately according to the application and purpose so as not to cause problems such as gum-up and roll fogging. The printing on the substrate can be performed using known methods such as flat screen printing and rotary screen printing. In the case of screen printing, it is also preferable to attach the screen fabric obliquely to the frame, for example at 45° or 60°, to prevent moire.

[0041] The above organic solvent immersion test is carried out in a draft chamber capable of local ventilation. After immersion in an organic solvent for 24 hours, if the weight is reduced, it is considered to have been dissolved; if the weight is increased, it is considered to have been swollen; if the weight is unchanged, it is considered to have been neither swollen nor dissolved. By configuring the PPS fabric of the present invention as described above, the weight change rate after immersion in each of cyclohexanone and isophorone solvents for 24 hours in an environment of a temperature of 20±2°C and a relative humidity of 65±5% RH can be less than 3.0%, and this makes it possible to obtain a fabric that is suitable for screen printing using solvent ink and precision filtration of organic solvents, which does not experience a decrease in strength due to swelling during use of solvent ink, and does not experience changes in line diameter or mesh size due to swelling or dissolution.

[0042] The finished PPS fabric of the present invention is inspected and then used for products such as filters, filter cloths, strainers, screens, and electrical insulating materials, but if the inspection reveals defects such as poor appearance or holes, the filtration performance of the parts is reduced and the fabric cannot be used as a product. Therefore, in order to increase the product yield, it is important that there are as few hole defects as possible, there is little variation in mesh opening, and the unevenness of the woven fabric surface is uniform. It is preferable that there are 10 or less partial defects such as holes within a length of 50 m, and it is not preferable that there is variation in mesh opening, surface unevenness, etc., which results in poor appearance as an overall quality.

[0043] The applications of the PPS woven fabric of the present invention include filters, filter cloths, strainers, screens, and electrical insulating materials. Electrical insulating materials include applications to insulating separators for fuel cells and hydrogen generating devices. The main applications of filters, filter cloths, and strainers are separation applications such as gas / solid separation, liquid / solid separation, and solid / solid separation, while the main applications of screens are printing applications in which a dispersion in which fine particles are uniformly dispersed in a dispersion medium such as emulsion, suspension, or slurry is uniformly measured and applied. In either case, if the fibers are dissolved or swollen by a solvent or dispersion medium, the required function cannot be achieved. In addition, electrical insulating materials are applications that utilize the characteristics of PPS, such as heat resistance, chemical resistance, hydrolysis resistance, and flame retardancy. If necessary, the woven fabric can be subjected to special processing such as water repellency and flame retardancy after scouring, and can also be resin-treated with epoxy resins, methylol melamine resins, phenolic resins, etc. In addition, it can be used as a multi-layer laminate such as two-ply, three-ply, or four-ply depending on the application purpose. When making a multi-layer laminate, for example in the case of a three-ply structure, stacking the weft and warp threads staggered to provide 0°, +45° bias, and -45° bias will improve the separation efficiency when used as a filter or filtration cloth. EXAMPLES

[0044] The effects of the present invention will be shown by the following examples, but the present invention is not limited thereto. The methods for evaluating the respective characteristic values ​​of the present invention are as follows.

[0045] (fineness) The corrected fineness was determined based on Method A described in 8.3.1a) of JIS L-1013 (2010 edition).

[0046] (single fiber diameter) The PPS long fiber filament was embedded in epoxy resin, frozen using a Reichert FC-4E cryosectioning system, and cut using a Reichert-Nissei ultracut N (ultramicrotome) equipped with a diamond knife. The cut surface was then photographed using a Hitachi H-7100FA transmission electron microscope (TEM) at a magnification that allowed the entire long fiber filament to be observed. The fiber diameter (μmφ) of all single fibers was measured from this image using image processing software. Measurements were taken for 10 randomly selected points on the PPS long fiber filament, and the average value of the 10 points was calculated.

[0047] (Confirmation of tensile strength, elongation and yield point) The tensile strength and elongation were calculated according to the standard test method described in 8.5.1 of JIS L-1013, 2010. The test machine was a slow-speed extension type, the grip distance was 20 cm, and the tensile speed was 20 cm / min. A chart of the stress-strain curve was created, and the tensile strength, elongation (elongation at break), and yield point were read from the chart. The arithmetic average of 10 trials was used as the measured value.

[0048] (Viscoelasticity measurement) The dynamic viscoelasticity measuring device DMA Q800 manufactured by TA Instruments was used, and the evaluation was performed in the measurement temperature range of 20°C to 250°C, with a measurement frequency of 0.5Hz and a heating rate of 2°C / min. The test sample was prepared by arranging the fibers so that it had a length of about 10mm, a width of about 7mm, and a thickness of 0.15mm. Tanδmax, which is the maximum value of the mechanical loss tangent Tanδ, which is a viscoelastic structural parameter, is the peak value in the obtained Tanδ profile, and the ambient temperature at that time was taken as Tmax (°C).

[0049] (Birefringence) Using a Nikon polarizing microscope POH type, a Leitz Berek compensator, and a Toshiba spectrum light source starter SLS-3-B type (sodium light source), a fiber with a length of 5 to 6 mm was cut at an angle of 45° to the fiber axis as a sample, adjusted so that the cut surface was facing up on the stage of the polarizing microscope, an analyzer was inserted to make it a dark field, and the number of fringes was counted with the compensator at 30. (n pieces) The compensator was turned in the right-hand screw direction to measure the compensator scale a where the sample first became the darkest, and the compensator was turned in the left-hand screw direction to measure the compensator scale b where the sample first became the darkest (both were read to 1 / 10 scale). Furthermore, the compensator was returned to 30, the analyzer was removed, the diameter d of the sample was measured, and the birefringence (Δn) was calculated based on the following formula (average of 20 measurements). Δn=T / d(T=nλ0+ε) λ0=589.3mμ (where ε is calculated from C / 1000 and i in the Leitz compensator manual, and i is (ab) (the difference in compensator readings).)

[0050] (Weight average molecular weight) The weight average molecular weight of the PPS polymer and PPS fiber was calculated in terms of polystyrene using gel permeation chromatography (GPC), a type of size exclusion chromatography. The measurement conditions are as follows: Equipment: Senshu Scientific SSC-7110 Column name: Showa Denko Shodex UT-806M, 2 columns in series Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL (slurry: approx. 0.2% by weight)

[0051] (Finished density) The warp and weft density of the finished fabric was measured according to JIS L1096:2010 8.6 Density method.

[0052] (Opening size) The mesh size A (μm) was calculated using the following formula. The wire diameter d (μm) used in this calculation was calculated based on the following formula. However, the formula for calculating the wire diameter d (μm) is applicable only to round cross-section yarns, and the specific gravity SG of PPS is 1.35 g / cm 3 For polyamide 6, the value is 1.12 g / cm 3 The value of was used. A(μm)={25.4 / [warp or weft density (threads / inch)]}×1000-d d(μm)=11.91×√[(fineness(dtex)÷1.11) / SG] In the present invention, when the yarn comprises a plurality of fibers, the wire diameter d is calculated assuming that the yarn comprises a single fiber (approximately a monofilament).

[0053] (Opening ratio) The aperture ratio ε (%) was calculated using the following formula. ε(%)=[A / (A+d)] 2 ×100

[0054] (Fabric shrinkage rate in boiling water) The woven fabric sample was cut into a square of approximately 50 cm square, and marks were made at 200 mm intervals along the warp and weft threads, followed by boiling treatment in hot water at 98±2°C for 30 minutes. After boiling treatment, the sample was removed from the hot water, spread on a paper filter, and air-dried on a flat surface. After air-drying, the length L mm of the marks made in the warp and weft directions was measured, and the boiling water shrinkage (SHW(%)) in the warp and weft directions was evaluated using the following formula. The arithmetic average of five measurements was taken as the measured value. SHW(%)=[(200-L) / 200]×100

[0055] (Changes in aperture ratio when dry-heat treated at 160℃) The opening rate OP1 (%) of the PPS fiber before the dry heat treatment to be used as the sample was confirmed. Then, a constant temperature incubator DKN303 manufactured by Yamato Scientific Co., Ltd. and a mesh fabric using para-aramid fiber (trade name Technora) manufactured by Teijin Co., Ltd. in the warp and weft directions were used, and the para-aramid mesh fabric was horizontally installed inside the constant temperature incubator. The sample (PPS fabric) was placed horizontally on the para-aramid mesh fabric so as not to come into contact with the metal parts such as the metal inner wall and shelves of the incubator, and a dry heat treatment was performed for 30 minutes at 160°C. After that, the PPS fabric sample was taken out with the mesh fabric placed on it and cooled at room temperature, and the opening rate OP2 (%) of the PPS fiber after the dry heat treatment was confirmed, and the variation in the opening rate was calculated according to the following formula. However, the opening rate (%) before and after the treatment was the average value of 10 measurement points. Variation in aperture ratio (%) = |OP1-OP2| / OP1×100

[0056] (Weight change rate after immersion in organic solvent) Two stainless steel trays, 30 cm long, 15 cm wide, and 5 cm deep, were prepared in a draft chamber that was set up in a room with a temperature control of 20±2°C and a relative humidity control of 65±5%RH and was set up so that local exhaust could be achieved by negative pressure suction. 300 ml of cyclohexanone and isophorone were poured into each tray, and a weighed PPS fabric was immersed in the tray. After 24 hours, the tray was removed, air-dried on absorbent paper for 5 minutes, and then weighed to confirm the weight change before and after immersion. The weight change rate (%) was calculated from the weight A (g) before immersion and the weight B (g) after immersion according to the following formula: Weight change rate (%) = |AB| / A x 100

[0057] (fabric quality) The example fabrics, 100cm wide and 50m long, were finished and visually inspected using an inspection machine to evaluate the results. Fabrics with more than 10 holes or defects within the 50m length, large variations in mesh size, or overall wrinkled surface irregularities and other poor appearances were deemed to have failed.

[0058] (comprehensive evaluation) The changes in the opening size and aperture ratio of the fabric before and after shrinkage in boiling water were evaluated, and the presence or absence of unevenness in the opening size and aperture ratio of the fabric, as well as the uneven wrinkles that appeared on the fabric after shrinkage in boiling water, were visually checked, and the overall quality was evaluated in the following three categories. 〇…Good quality △…Some quality concerns but pass ×…Poor quality, fail In addition, defects such as holes in more than 10 places were marked with ××, and defects without defects were marked with ◯ to evaluate the frequency of occurrence of partial defects. The worse evaluation result of either the overall quality or the partial defects was used as the overall evaluation.

[0059] Example 1 PPS raw resin (linear type, weight average molecular weight 51500) pellets were vacuum dried for 12 hours using a vacuum dryer set at an atmospheric temperature of 160°C, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline, and subjected to two-stage hot drawing in a bath, followed by a constant-ratio relaxation heat treatment, and then split into individual monofilaments using a splitting machine to obtain a PPS long fiber monofilament. The surface temperature of the stretching preheating roller was set to 90°C, the drawing temperature was set to 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing was set to 180°C, and the total draw ratio was set to 3.0 times, to obtain a PPS long fiber 33 dtex monofilament.

[0060] The PPS long fiber filaments were used in both warps and wefts to weave a plain weave fabric. The resulting fabric was beaten, scoured and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C, then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The properties are shown in Table 1. The resulting fabric showed little change in fabric dimensions, mesh opening and aperture ratio after boiling water treatment. A solvent-based screen ink was prepared and used as a screen for a flat screen printing machine equipped with an explosion-proof structure and a local exhaust device to print the fabric. There was no swelling or dissolution due to the solvent, no clogging, and no twisting or holes caused by the squeegee, and the fabric was finished to be suitable for screen printing.

[0061] Example 2 Using a vacuum dryer set at an atmospheric temperature of 160°C, pellets of PPS raw resin (linear type, weight average molecular weight 51500) were vacuum dried for 12 hours, and then PPS long fiber monofilament was obtained by the air gap spinning method at a spinning temperature of 300°C. The cooling water bath temperature was 50±2°C, the air gap was 30 mm, the surface temperature of the stretching preheating roller was 90°C, the stretching temperature was 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after stretching was 180°C, and the total stretch ratio was 5.0 times, and 2 filaments of PPS long fiber 33 decitex were obtained.

[0062] The PPS long fiber filaments were used in both warp and weft directions to weave a 2 / 2 twill weave fabric. The resulting fabric was beaten, scoured and relaxed at a bath temperature of 90°C using a continuous water washer with a spread roller type equipped with an ultrasonic cleaning mechanism, and then introduced into a weave straightening device, pre-dried with a heat cylinder with a surface temperature of 120°C, and finished and set with a heat setter with an atmospheric temperature adjusted to 180°C. The properties are shown in Table 1. The resulting fabric showed little change in fabric dimensions, mesh opening and opening ratio after boiling water treatment. The resulting fabric was used as a material for the screen unit of the cylindrical screen of a classification sieve (turbo screener) and used for classification of aluminum hydroxide powder. Dry classification was possible without any operational problems.

[0063] Example 3 Using a vacuum dryer set at an atmospheric temperature of 160°C, PPS raw resin (linear type, weight average molecular weight 51500) pellets were vacuum dried for 12 hours, and then 33 dtex PPS long fiber filaments were obtained by spinning and stretching (spin draw method). The spinning temperature was 310°C, the stretching preheat roller temperature was 100°C, and the total stretch ratio was 1.6 times.

[0064] The PPS long fiber filaments were used in both the warp and weft directions to weave a 2 / 2 twill weave fabric. The resulting fabric was beaten, scoured and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C, then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The properties are shown in Table 1. The resulting fabric showed little change in fabric dimensions, mesh opening and aperture ratio after boiling water treatment. The resulting fabric was impregnated with epoxy resin to form a substrate for printed circuit boards for electronic devices. A material suitable for substrates that is thin, does not take up much space, and has excellent electrical insulation properties was obtained.

[0065] Example 4 Using a vacuum dryer set at an atmospheric temperature of 160°C, PPS raw material resin (linear type, weight average molecular weight 51500) Repetto was dried for 12 hours, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline and subjected to two-stage hot drawing in air and then a constant-ratio relaxation heat treatment to obtain 33 dtex 4 filaments of PPS long fiber. The surface temperature of the drawing preheat roller was set to 90°C, the drawing temperature to 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing to 180°C, and the total draw ratio to 3.0 times.

[0066] The PPS long fiber filaments were used in both warp and weft to weave a 1 / 2 twill weave greige fabric. The greige fabric was beaten, scoured and relaxed at a bath temperature of 90°C using a continuous spread-roller type water washer equipped with an ultrasonic cleaning mechanism, and then introduced into a weave straightening device, pre-dried with a heat cylinder with a surface temperature of 120°C, and finished and set with a heat setter adjusted to an atmospheric temperature of 180°C. The properties are shown in Table 1. The fabric obtained showed little change in the fabric dimensions, mesh opening and opening rate after boiling water treatment. The fabric obtained was used as a heat-resistant air filter. It had excellent heat resistance and chemical resistance, and was suitable as a primary collection filter for air containing chemical mist, dust, and dirt.

[0067] Example 5 Using a vacuum dryer set at an atmospheric temperature of 160°C, PPS raw material resin (linear type, weight average molecular weight 51500) Repetto was dried for 12 hours, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline and subjected to two-stage hot drawing in air and then a constant-ratio relaxation heat treatment to obtain a PPS long fiber 33 dtex 3 filament. The surface temperature of the drawing preheat roller was set to 90°C, the drawing temperature to 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing to 180°C, and the total draw ratio to 3.0 times.

[0068] The PPS long fiber filaments were used in both warps and wefts to weave a plain weave fabric. The resulting fabric was beaten, scoured and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C, then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The properties are shown in Table 1. The resulting fabric showed little change in fabric dimensions, mesh opening and aperture ratio after boiling water treatment. A solvent-based screen ink was prepared and used as a screen for a flat screen printing machine equipped with an explosion-proof structure and a local exhaust device to print the fabric. There was no swelling or dissolution due to the solvent, no clogging, and no twisting or holes caused by the squeegee, and the fabric was finished to be suitable for screen printing.

[0069] Example 6 Using a vacuum dryer set at an atmospheric temperature of 160°C, pellets of PPS raw resin (linear type, weight average molecular weight 51,500) were vacuum dried for 12 hours, and then a PPS long fiber monofilament was obtained by the air gap spinning method at a spinning temperature of 300°C. The cooling water bath temperature was 50±2°C, the air gap was 30 mm, the surface temperature of the stretching preheating roller was 90°C, the stretching temperature was 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after stretching was 180°C, and the total stretch ratio was 5.0 times, resulting in a PPS long fiber monofilament of 33 dtex.

[0070] The PPS long fiber filaments were used in both the warp and weft directions to weave an eight-ply weft and satin weft (1 / 7 (5 filaments)). The resulting greige fabric was beaten, refined and relaxed at a bath temperature of 90°C using a continuous spread-roller type water washer equipped with an ultrasonic cleaning mechanism, and then introduced into a weave straightening device, where it was pre-dried using a heat cylinder with a surface temperature of 120°C, and then finished and set using a heat setter with an atmospheric temperature adjusted to 180°C. The property values ​​are shown in Table 1. The resulting fabric was used as a filter cloth for a filter press. The solid-liquid separation of the slurry liquid was smooth, and the cake separation was also good, making it suitable as a filter cloth for a filter press.

[0071] Example 7 Using a vacuum dryer set at an atmospheric temperature of 160°C, PPS raw material resin (linear type, weight average molecular weight 51500) Repetto was dried for 12 hours, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline and subjected to two-stage hot drawing in air and then a constant-ratio relaxation heat treatment to obtain a PPS long fiber 33 dtex 3 filament. The surface temperature of the drawing preheat roller was set to 90°C, the drawing temperature to 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing to 180°C, and the total draw ratio to 3.0 times.

[0072] The PPS long fiber filaments were used in both the warp and weft directions and woven into a five-ply twill weave (4 / 1 (3-way)). The resulting greige fabric was beaten and refined and relaxed at a bath temperature of 90°C using a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism, then introduced into a weave straightening device, pre-dried with a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The property values ​​are shown in Table 1. The resulting fabric was used as a filter cloth for a filter press. The solid-liquid separation of the slurry liquid was smooth and the cake separation was also good, making it suitable as a filter cloth for a filter press.

[0073] Comparative Example 1 PPS raw resin (linear type, weight average molecular weight 51500) pellets were vacuum dried for 12 hours using a vacuum dryer set at an atmospheric temperature of 160°C, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline, and subjected to two-stage hot drawing in a bath, followed by a constant-ratio relaxation heat treatment, and then split into individual monofilaments using a fiber splitter to obtain a PPS long fiber monofilament. The surface temperature of the drawing preheat roller was set to 85°C, the drawing temperature was set to 90±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing was set to 180°C, and the total draw ratio was set to 1.8 times to obtain a PPS long fiber 55 dtex monofilament.

[0074] The PPS long fiber filaments were used in both the warp and weft directions to weave a plain weave greige fabric. The greige fabric was beaten and then refined and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C. It was then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The property values ​​are shown in Table 1. The opening rate of the fabric after boiling water treatment and after dry heat treatment at 160°C varied greatly, and the surface was uneven. In addition, the openings were non-uniform, making it unsuitable for use as a screen, filter, or electrical insulating material.

[0075] Comparative Example 2 Using a vacuum dryer set at an atmospheric temperature of 160°C, pellets of PPS raw resin (linear type, weight average molecular weight 51500) were vacuum dried for 12 hours, and then a PPS long fiber monofilament was obtained by the air gap spinning method at a spinning temperature of 300°C. The cooling water bath temperature was 50±2°C, the air gap was 50 mm, the surface temperature of the stretching preheating roller was 90°C, the stretching temperature was 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after stretching was 150°C, and the total stretch ratio was 4.0 times, resulting in a PPS long fiber 75 dtex monofilament.

[0076] The PPS long fiber filaments were used in both warp and weft directions to weave a 2 / 2 twill weave greige fabric. The greige fabric was beaten and then refined and relaxed at a bath temperature of 90°C using a continuous spread-roller type water washer equipped with an ultrasonic cleaning mechanism, then introduced into a weave straightening device, pre-dried with a heat cylinder with a surface temperature of 120°C, and finished and set with a heat setter adjusted to an atmospheric temperature of 180°C. The properties are shown in Table 1. The opening rate fluctuation after the boiling water treatment and the opening rate fluctuation after the dry heat treatment at 160°C were both somewhat large, and there was variation in the opening. The weave was 2 / 2 twill, and the surface unevenness was not significant, but the fabric was not suitable for the intended uses of the present invention, such as screens, filters, and electrical insulation materials.

[0077] Comparative Example 3 Using a vacuum dryer set at an atmospheric temperature of 160°C, PPS raw resin (linear type, weight average molecular weight 51500) pellets were vacuum dried for 12 hours, and then spinning and stretching (spin draw method) were performed to obtain PPS long fiber 33 dtex 18 filaments. The spinning temperature was 310°C, the stretching preheating roller temperature was 100°C, and the total stretch ratio was 1.6 times.

[0078] The PPS long fiber filaments were used in both the warp and weft directions to weave a 2 / 2 twill weave greige fabric. The greige fabric obtained was beaten, scoured and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C, then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The property values ​​are shown in Table 1. The obtained fabric showed little change in fabric dimensions, mesh size and opening ratio after boiling water treatment, but showed a somewhat large weight change after immersion in cyclohexanone and isophorone, and was not suitable for the intended uses of the present invention, such as screens, filters and electrical insulation materials.

[0079] Comparative Example 4 PPS raw resin (linear type, weight average molecular weight 51500) pellets were vacuum dried for 12 hours using a vacuum dryer set at an atmospheric temperature of 160°C, and then melt spun at a spinning temperature of 300°C by a known melt spinning method to obtain an undrawn PPS long fiber filament yarn. The undrawn yarn was introduced into a drawing machine offline, and subjected to two-stage hot drawing in a bath, followed by a constant-ratio relaxation heat treatment, and then split into individual monofilaments using a fiber splitter to obtain a PPS long fiber monofilament. The surface temperature of the drawing preheat roller was set to 90°C, the drawing temperature was set to 95±3°C, the temperature inside the chamber in the relaxation heat treatment area after drawing was set to 180°C, and the total draw ratio was set to 10.0 times, to obtain a PPS long fiber 33 dtex 6 filament.

[0080] The PPS long fiber filaments were used in both the warp and weft directions to weave a 2 / 2 twill weave greige fabric. The greige fabric obtained was beaten, scoured and relaxed in a spread-roller type continuous water washer equipped with an ultrasonic cleaning mechanism at a treatment bath temperature of 90°C, then introduced into a weave straightening device, pre-dried in a heat cylinder with a surface temperature of 120°C, and finished and set in a heat setter with an atmospheric temperature adjusted to 180°C. The properties are shown in Table 1. The fabric was thermally stable and had good stability against ketone-based chemicals, but the stretch ratio of the fiber was too high, resulting in low toughness and causing holes with even slight deformation, making it unsuitable for the intended uses of the present invention, such as screens, filters, and electrical insulation materials.

[0081] Comparative Example 5 The raw polyamide 6 resin pellets were vacuum-dried for 12 hours using a vacuum dryer set at an atmospheric temperature of 110°C, and then subjected to spinning direct drawing (spin-draw method) to obtain polyamide 6 long fiber 33 decitex 1 filament. The spinning temperature was 250°C, and the total draw ratio was 1.6 times.

[0082] The polyamide 6 filament filaments were used in both warps and wefts to weave a plain weave fabric. The resulting fabric was beaten, scoured and relaxed at a bath temperature of 80°C using a continuous water washer with a spreading roller equipped with an ultrasonic cleaning mechanism, and then introduced into a weave straightening device, pre-dried with a heat cylinder with a surface temperature of 100°C, and finished and set with a heat setter adjusted to an atmospheric temperature of 150°C. The properties are shown in Table 1. The boiling water shrinkage of the fabric remained somewhat high, but the opening rate fluctuated greatly after dry heat treatment at 160°C, resulting in a large variation in the opening rate. In addition, the fibers swelled when immersed in cyclohexanone and isophorone, and the opening rate and opening rate were also significantly varied, and the strength was not favorable, making the fabric unsuitable for the intended uses of the present invention, such as screens, filters, and electrical insulation materials.

[0083] Comparative Example 6 Spinning was attempted in the same manner as in Example 1, except that the PPS resin was changed from linear to crosslinked. However, stable spinning operating conditions could not be obtained due to a gradual increase in pressure loss over time, and as a result, fibers could not be obtained.

[0084] [Table 1] [Industrial Applicability]

[0085] The PPS fabric of the present invention has the characteristics of PPS resin, such as heat resistance, chemical resistance, and flame retardancy, and further has improved mechanical strength and dimensional stability by controlling the physical properties of the yarn, etc. Taking advantage of these characteristics, the PPS fabric of the present invention can be used safely and stably in a wide range of applications, such as screens, filters, and electrical insulating materials including battery separators and partition walls of hydrogen generating devices, making it extremely useful in this industry.

Claims

1. A woven fabric comprising polyphenylene sulfide long fiber filaments having a single yarn fineness of 2 dtex or more and 50 dtex or less, a constituent single yarn number of 1 to 4, and a total fineness of 2 dtex or more and 200 dtex or less, arranged as warp yarns and / or weft yarns, the polyphenylene sulfide long fiber filaments being made of a linear type polyphenylene sulfide resin as a raw material, wherein the polyphenylene sulfide long fiber filaments have a maximum value Tanδmax of 0.02 to 0.05 at a measurement frequency of 0.5 Hz, which is a viscoelastic structural parameter of the amorphous region of the polyphenylene sulfide long fiber filaments, and the atmospheric temperature Tmax at which Tanδ shows the maximum value is 130° C. or more and 160° C. or less, and A polyphenylene sulfide woven fabric characterized in that, in the tensile strength and elongation of polyphenylene sulfide long fiber filament specified in L1013.8.5.1 (standard time test), the stress-strain curve has a yield point and the breaking elongation is 15% or more and 35% or less.

2. 2. The polyphenylene sulfide woven fabric according to claim 1, characterized in that the polyphenylene sulfide long fiber filaments have a circular fiber cross section, a single fiber diameter of the polyphenylene sulfide long fiber filaments is 15 μmφ or more and 70 μmφ or less, and a birefringence Δn of the polyphenylene sulfide long fiber filaments is 0.100 or more and 0.300 or less.

3. 2. The polyphenylene sulfide fabric according to claim 1, characterized in that the polyphenylene sulfide fabric has a weave structure of any one of plain weave, twill weave, and satin weave, the mesh size of the polyphenylene sulfide fabric is 1 μm or more and 200 μm or less, and the opening ratio of the polyphenylene sulfide fabric is 10% or more and 60% or less.

4. 4. The polyphenylene sulfide fabric according to claim 1, wherein the opening rate of the polyphenylene sulfide fabric before and after dry heat treatment for 30 minutes at a treatment temperature of 160°C is within ±3% when the fabric is placed horizontally and stationary, and the weight change rate of the polyphenylene sulfide fabric after immersing the fabric in each of cyclohexanone and isophorone solvents for 24 hours in an environment of a temperature of 20±2°C and a relative humidity of 65±5%RH is less than 3.0% in both cases.

5. A screen using the polyphenylene sulfide fabric according to claim 1.

6. A filter comprising the polyphenylene sulfide fabric according to claim 1.

7. An electrical insulating material comprising the polyphenylene sulfide fabric according to claim 1.

Citation Information

Patent Citations

  • Fine-size polyphenylene sulfide monofilament and method for producing the same

    JP2009068149A

  • Method for producing polyphenylene sulfide fibers

    JP2022157916A

  • Composite electrolyte membrane

    WO2019188960A1

  • JP2018‐534441B

  • Heat-resistant non-woven fabric

    WO2008035775A1